Aplicação de zeólita mesoporosa sintetizada utilizando quitina para a adsorção de corantes catiônicos - Brião, Giani de Vargas (2018)
Zeolites are microporous materials, in general, which hinder the diffusive transport of certain molecules. Thus, to increase the possibilities of applications of this material, some studies proposed an addition of mesoporosity agents in zeolite synthesis. This work aims to apply the modified ZSM-5 zeolite by the addition of chitin (chitin / ZSM-5) in the adsorption of cationic dyes. The strategy for the studies was to compare the adsorption capacity of the crystal violet (CV) in chitin/ZSM-5 and ZSM-5 zeolites, and once an improvement of the adsorption capacity by the presence of the mesoporos was verified, the tests would be continued with other dyes: methylene blue (MB) and basic fuchsin (BF). In the synthesis of the zeolite, synthesis gel and gel precursor was employed and, before the calcination stage, chitin was added. For the characterization, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), nitrogen adsorption (BET and BJH) and X-ray diffraction (XRD) were used. The experiments of adsorption were based on the kinetics, equilibrium isotherm and thermodynamic studies. In addition, experiments with simulated textile effluent and regeneration and reuse of the adsorbent were also performed. The results of the characterization showed that chitin / ZSM-5 zeolite presented more adequate characteristics for adsorption than ZSM-5 zeolite synthesized by pattern route, because with the chitin addition: the crystallinity decreased; the total pore volume increased 25%; the volume of mesopores increased 5 times and the mean diameter of the pores increased 11 times. These changes in the zeolite structure caused the maximum CV adsorption capacity to increase from 141.8 (ZSM-5) to 1217.3 mg g -1 (chitin / ZSM-5). The results for comparison of the adsorption of methylene blue, basic fuchsin and violet crystal on chitin / ZSM-5 showed that the operation was favored using the adsorbent dosage of 2.0 g L-1 and pH of 7.5, 8.0 and 9.0 for CV, MB and BF, respectively. The intraparticle diffusion model was adequate to represent the kinetic profile, providing intraparticle diffusion coefficients of 6.36 × 10-14, 1.36 × 10-13 and 1.37 × 10-13 m² min-1 for CV, MB and BF. Equilibrium was described by Sips (Methylene Blue and Basic Fuchsin) and Langmuir for Violet Crystal. The adsorption was spontaneous, favorable and endothermic. The maximum adsorption capacities were 1217.3, 548.2 and 237.5 mg g-1 for CV, MB and BF, respectively. The proposed regeneration process (calcination at 600 ° C) was efficient because the adsorbent can be reused fifteen times maintaining the same adsorption capacity. Chitin / ZSM-5 was efficient to remove the color from simulated textile effluent. In summary, the adsorbent synthesized using as mesoporosity agent an efficient, economical and capable material to adsorbing cationic dyes.